A qualitative exploration of roles and expectations of male partners from PMTCT services in rural Malawi - Beatrice M'baya Kansinjiro; Alinane Linda Nyondo-Mipando (BMC, 2021)
Abstract Background Prevention of mother-to-child transmission of HIV (PMTCT) is effective in curbing rates of HIV infection in children because its interventions reduce the rates of transmission during pregnancy, in labour, and in breastfeeding. Male involvement (MI) greatly influences uptake and adherence to PMTCT services. Lack of clarity on the roles and expectations of men in PMTCT is one of the main barriers to MI. The main aim of the study was to explore the roles and expectations of male partners from PMTCT services in Malawi. Methods This was a descriptive qualitative study that involved men whose partners were either pregnant or breastfeeding a child, health care workers working in PMTCT services for over six months, and traditional leaders. We conducted 9 in-depth interviews and 12 key informant interviews from January to March 2018. All interviews were audio-recorded, transcribed, and translated. Thematic analysis was employed to analyze data. Results The subjective and community norms and attitudes of men towards PMTCT provide the context in which male partners define the specific roles they render and the services they expect from PMTCT services. The roles of men in PMTCT service were contextualized in what is socially acceptable and normalized in the setting and include supportive roles expressed as accompanying the wife to attend; antenatal care services, Dry blood sample collection (DBS) when its due, keeping appointments when is due to take the ARVs, providing financial support; HIV prevention behavior change and decision-making roles. The desired services within PMTCT include health assessment such as checking their weight; blood pressure; blood sugar and promotion activities such as education sessions that are provided in a male-friendly manner that is in tandem with existing socio-cultural norms and attitudes of men towards such services. Conclusion The roles of male partners in PMTCT services are underpinned by subjective norms and what is socially acceptable within a specific context. The services that men require from PMTCT services are influenced by their attitudes and beliefs towards PMTCT interventions. Services should be male-tailored provided in an atmosphere that allows and accepts male partners to exercise their roles in PMTCT services.